2004
DOI: 10.1007/s00234-004-1196-0
|View full text |Cite
|
Sign up to set email alerts
|

MRI language dominance assessment in epilepsy patients at 1.0�T: region of interest analysis and comparison with intracarotid amytal testing

Abstract: The primary goal of this study was to test the reliability of presurgical language lateralization in epilepsy patients with functional magnetic resonance imaging (fMRI) with a 1.0-T MR scanner using a simple word generation paradigm and conventional equipment. In addition, hemispherical fMRI language lateralization analysis and region of interest (ROI) analysis in the frontal and temporo-parietal regions were compared with the intracarotid amytal test (IAT). Twenty epilepsy patients under presurgical evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 25 publications
1
54
0
1
Order By: Relevance
“…These studies are listed in Table 2 with a description of the task employed, region of interest, subject sample size, number of participants with atypical language, concordance or correlation, and activation patterns (Baciu et al 2001;Bahn et al 1997;Benke et al 2006;Benson et al 1999;Binder et al 1996;Carpentier et al 2001;Deblaere et al 2004;Desmond et al 1995;Gaillard et al 2002Gaillard et al , 2004Hertz-Pannier et al 1997;Lehericy et al 2000;Liegeois et al 2002;Rutten et al 2002;Sabbah et al 2003;Spreer et al 2002;Woermann et al 2003;Worthington et al 1997;Yetkin et al 1998). The IAT (Wada 1949) is used routinely and considered the "gold standard" for language lateralization prior to epilepsy surgery, though the procedure provides no information about localization within a hemisphere.…”
Section: Comparisons Between Fmri and The Intracarotid Amobarbital Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are listed in Table 2 with a description of the task employed, region of interest, subject sample size, number of participants with atypical language, concordance or correlation, and activation patterns (Baciu et al 2001;Bahn et al 1997;Benke et al 2006;Benson et al 1999;Binder et al 1996;Carpentier et al 2001;Deblaere et al 2004;Desmond et al 1995;Gaillard et al 2002Gaillard et al , 2004Hertz-Pannier et al 1997;Lehericy et al 2000;Liegeois et al 2002;Rutten et al 2002;Sabbah et al 2003;Spreer et al 2002;Woermann et al 2003;Worthington et al 1997;Yetkin et al 1998). The IAT (Wada 1949) is used routinely and considered the "gold standard" for language lateralization prior to epilepsy surgery, though the procedure provides no information about localization within a hemisphere.…”
Section: Comparisons Between Fmri and The Intracarotid Amobarbital Testmentioning
confidence: 99%
“…Several studies have reported higher concordance rates using frontal rather than temporoparietal ROIs (Benke et al 2006;Deblaere et al 2004;Spreer et al 2002). Deblaere et al (2004) examined the concordance between IAT and fMRI LIs from various ROIs including whole hemisphere, frontal and temporalparietal using a 1.0 Tesla magnet. They used a covert word chain task where subjects were instructed to generate a list of words starting with the last letter of the previous word.…”
Section: Comparisons Between Fmri and The Intracarotid Amobarbital Testmentioning
confidence: 99%
“…The laterality index was deemed left dominant when LI > .20, and right dominant when LI b −.20, and values in-between were considered bilateral (Deblaere et al, 2004;Springer et al, 1999).…”
Section: Brain Laterality In the Processing Of Numbers And Mathematicmentioning
confidence: 99%
“…A more unexpected result was observed in TPG, which demonstrated inconsistent laterality across subjects, although this region is widely believed to be an important receptive language center (Baldo et al 2006;Kamada et al 2006;Ross 1980;Wernicke 1874). While somewhat unexpected, this observation is supported by many reports documenting inconsistent laterality in the posterior temporal lobe derived by fMRI (Bahn et al 1997;Deblaere et al 2004;Lehericy et al 2000;Spreer et al 2002). However, other functional modalities such as positron emission tomography (PET) and magnetoencephalography (MEG) typically report strong leftward asymmetry of activation in this region, consistent with typically lateralized language processing (Kober et al 2001;Muller et al 1997;Papanicolaou et al 1999;Shapiro et al 2005;Simos et al 1998;Szymanski et al 1999).…”
Section: Threshold-independence In LI Assessmentmentioning
confidence: 58%